2006
DOI: 10.1002/anie.200503035
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Isolation of Functional Organic Nanotubes

Abstract: The last straw: Sonication of C‐hexylpyrogallol[4]arene with pyrene, acetonitrile, and water results in the formation of crystalline organic nanotubes. Alternating pockets of acetonitrile and water are contained within the large internal diameter of the tube formed by the calixarenes (see picture; the tube and solvent molecules are shown as stick and space‐filling representations, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(60 citation statements)
references
References 25 publications
0
60
0
Order By: Relevance
“…273 c. Nanoparticles Atwood and co-workers 274 have demonstrated the formation of C-n-hexylpyrogallol [4]arene-based organic nanotubes in the solid state that show some potential to maintain their structure in solution. C-Undecylcalix [4]resorcinarene-capped anatase (TiO 2 ) nanoparticles have been synthesized; they could be isolated and then redispersed in different nonaqueous solvents.…”
Section: B Fluorescencementioning
confidence: 99%
“…273 c. Nanoparticles Atwood and co-workers 274 have demonstrated the formation of C-n-hexylpyrogallol [4]arene-based organic nanotubes in the solid state that show some potential to maintain their structure in solution. C-Undecylcalix [4]resorcinarene-capped anatase (TiO 2 ) nanoparticles have been synthesized; they could be isolated and then redispersed in different nonaqueous solvents.…”
Section: B Fluorescencementioning
confidence: 99%
“…9 Recent studies have shown that PgCs self‐assemble into a wide range of supramolecular capsules based on both inter‐ and intramolecular hydrogen bonding,10 as well as metal ion coordination 1114. The guests in such capsules are generally small, polar molecules, but larger entities such as substituted pyrenes may also be housed in tubular15 structures and hexameric capsules 16. We now show that ferrocene can be used as a template towards the formation of a capsular motif.…”
mentioning
confidence: 99%
“…These hexamers pack in parallel to the crystallographic c axis and form monomolecular channels of diameter about 1 nm. This special supramolecular helical hexamer composing pure organic molecules is relatively rare [41][42][43]. It is also the first example of TB analogues reported.…”
Section: Crystal Engineering Of Novel Tb Analoguesmentioning
confidence: 96%